Disruptive Technology Factors Influencing Digital Recruitment Practices - Geetha R; Dr. Bhanu Sree Reddy D (International Journal of Advanced Science and Technology, 2020)
Purpose – The study examines the impact level of disruptive technology dimensions towards Digital Recruitment practices in industry. Disruptive technology is a part of Industry 4.0, which is lead by big data and its additional factors such as analytics, cloud computing, cyber security and artificial intelligence (Andrea Rojko,2018). In the words of Clayton Christensen(1995), who coined the term disruptive technology which means disruption is a process rather than a product or service. It also emphasis the importance of technology recruitment process held through artificial intelligence in current era.